Krupple-Like Factor 5 is a Potential Therapeutic Target and Prognostic Marker in Epithelial Ovarian Cancer - Siraj, Abdul K.; Pratheeshkumar, Poyil; Divya, Sasidharan Padmaja; Parvathareddy, Sandeep Kumar; Alobaisi, Khadija A.; Thangavel, Saravanan; Siraj, Sarah; Al-Badawi, Ismail A.; Al-Dayel, Fouad; Al-Kuraya, Khawla S. (Frontiers in Pharmacology, 2020)
Epithelial ovarian cancer (EOC) is the most lethal gynecological malignancy. Despite current therapeutic and surgical options, advanced EOC shows poor prognosis. Identifying novel molecular therapeutic targets is highly needed in the management of EOC. Krupple-like factor 5 (KLF5) is a zinc-finger transcriptional factor, is highly expressed in a variety of cancer type. However, its role and expression in EOC is not fully illustrated. Immunohistochemical analysis was performed to assess KLF5 protein expression in 425 primary EOC samples using tissue microarray. We also addressed the function of KLF5 in EOC and its interaction with signal transducer and activator of transcription 3 (STAT3) signaling pathway. We found that KLF5 overexpressed in 53% (229/425) of EOC samples, and is associated with aggressive markers. Forced expression of KLF5 enhanced cell growth in low expressing EOC cell line, MDAH2774. Conversely, knockdown of KLF5 reduced cell growth, migration, invasion and progression of epithelial to mesenchymal transition in KLF5 expressing cell lines, OVISE and OVSAHO. Importantly, silencing of KLF5 decreased the self-renewal ability of spheroids generated from OVISE and OVSAHO cell lines. In addition, downregulation of KLF5 potentiated the effect of cisplatin to induce apoptosis in these cell lines. These data reveals the pro-tumorigenic role of KLF5 in EOC and uncover its role in activation of STAT3 signaling pathway, suggesting the importance of KLF5 as a potential therapeutic target for EOC therapy.